2014
DOI: 10.1227/neu.0000000000000448
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plan Quality and Delivery Time Between Volumetric Arc Therapy (RapidArc) and Gamma Knife Radiosurgery for Multiple Cranial Metastases

Abstract: Background Volumetric modulated arc therapy (VMAT) has been shown feasible for radiosurgical treatment of multiple cranial lesions with a single isocenter. Objective To investigate whether equivalent radiosurgical plan quality and reduced delivery time could be achieved in VMAT for patients with multiple intracranial targets previously treated with Gamma Knife (GK) radiosurgery. Methods We identified 28 Gamma Knife treatments of multiple metastases. These were replanned for multi-arc (MA) and single-arc (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
176
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(186 citation statements)
references
References 27 publications
6
176
2
2
Order By: Relevance
“…[15][16][17] Although the selected cases in the present article were challenging by design, as shown in Table 3, we found reasonable agreement with other published data reported on radiation therapy delivery to multiple targets. 1,2,15,16,18 As seen in Table 3, the literature results generally fell within or very close to the 95% prediction band based on the model presented in Figure 3.…”
Section: Discussionsupporting
confidence: 90%
“…[15][16][17] Although the selected cases in the present article were challenging by design, as shown in Table 3, we found reasonable agreement with other published data reported on radiation therapy delivery to multiple targets. 1,2,15,16,18 As seen in Table 3, the literature results generally fell within or very close to the 95% prediction band based on the model presented in Figure 3.…”
Section: Discussionsupporting
confidence: 90%
“…Thomas et al. reported results for cases with 2–9 lesions and total tumor volumes from 0.23–19.56 cm 3 , all planned with 18 Gy prescriptions 4. Our preclinical cases had 2–8 lesions with a total tumor volume ranging from 1.09 to 26.95 cm 3 and most of the lesions were prescribed 21 Gy.…”
Section: Discussionmentioning
confidence: 75%
“…One study reported that VMAT plans provide superior conformity with no significant difference in dose fall off compared to Gamma Knife plans,4 whereas another study found that VMAT plans had comparable conformity to Gamma Knife but that Gamma Knife remained superior in terms of dose fall off around the target 9. Liu et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some studies have proposed treating multiple metastases with a single setup isocenter using volumetric modulated arc therapy (VMAT) technique 6 , 7 , 8 , 9 . However, the quality assurance and plan‐specific dose verification of a single‐isocenter multimetastases VMAT plan is a challenge to clinical physicists, due to the nature of small target volumes and low resolution detector arrays.…”
Section: Introductionmentioning
confidence: 99%